Effect of Annealing on Creep Behavior, Hardness, Roughness and Electrochemical Corrosion Parameters of Co- Cr Based Alloy - Bediwi, A. El; Kashita, Eman; M.Salman, Salah. M (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In the present work, the effect of annealing on creep behavior, hardness, maximum shear stress, roughness and electrochemical corrosion parameters of commercial Co64Cr29Mo6.5A0.5 (A= C, Si, Fe, and Mn) dental alloy from Travagliato (BS) - Italy have been studied and analyzed. Creep behavior was studied by indentation and stress exponent was determined by Mulheam-Tabor method. The results show that, Vickers hardness of Co64Cr29Mo6.5A0.5 alloy decreased but roughness parameters varied after annealing for two hours at 700, 800 and 900 -°C. Also the corrosion resistance in 0.5M HCl of Co64Cr29Mo6.5A0.5 alloy is increased but the corrosion rate with 0.5M HCl is decreased after annealing compared to normal alloy.